SOFRIMENTO E REDENÇÃO: A reprogramação corporal no reality show “Seca Você” - PASSOS, Andrea Ferreira (2024)
Contemporary society condemns the fat body, synonymous with self-mismanagement. Fatness carries a range of undesirable connotations. This dissertation explores how Maira Cardi's reality show "Seca Você" promotes the slim body as a health code. The objective of this study is to understand the regimes of visibility and bodily surveillance in contemporary times through the weight loss reality show. For heuristic purposes, we employ the approaches of the socioanthropological theory of the imaginary (MAFFESOLI, 1987, 1995, 1997, 1998, 2001, 2002, 2003, 2004, 2007, 2008, 2009, 2010, 2012, 2014, 2016, 2020; GOMES, 2016, 2017, 2019; MENDES, 2016a, 2016b; SILVA, 1997, 2001, 2007, 2010, 2020), highlighting Maffesoli's formism (MAFFESOLI, 1988, 1998, 2007, 2008, 2010), and Foucault's notion of biopower (1979, 1997a, 1197b, 1982, 1988, 2007). We use the Iramuteq tool, specifically the similarity tree, to underpin the investigation. The research corpus consists of four episodes of the reality show "Seca Você," published on Maíra Cardi's YouTube channel (2022), corresponding to the first season. We observe that the reality show plays a crucial role in disseminating psychologizing discourses, involving the interpretation and analysis of social phenomena from a psychological perspective. Additionally, the program reinforces the idea of individual self-responsibility, encouraging the belief that personal decisions and choices significantly determine one's life. Youtuber Maíra Cardi is seen as a anointed figure, entrusted with a mission, employing syncretic practices that blend elements of psychology, neopentecostalism, and entrepreneurship. The reality show "Seca Você" thus takes on the format of a liturgy, where the body is treated as a commodity to be managed with faith. The program configures itself as a biopolitical device, translating into continuous surveillance and control of bodies, as well as an imaginary technology, possessing its own strategies to seduce and fuel desires and sensations. The slim body, a contemporary totem, a sacralized object for the audience, takes the stage and enacts its best performance; an upgraded version of itself. Maira and her enchanting body make it seem possible for any woman to escape her mundane and problematic life, transforming into a goddess, as she herself refers to the participants. In an algophobic society, all conflicts must be purged, if possible, in the media scene where the happy ending must prevail, unlike ordinary life.